A mathematical model for determining timetables that minimizes the number of students with conflicting schedules - De Azevedo, Anibal Tavares; Kameyama, Alexander [UNESP]; Amorim, Joni A.; Gustavsson, Per M. (My University, 2013)
With the increasing complexity of educational initiatives, several challenges arise as to appropriately allocate human and material resources or how to select alternative investments within a portfolio. Due to the complexity, solutions based on intuition are risky, which leads to a search for less intuitive and more reliable ways of solving educational problems. An engineering approach to the problem may lead to operations research mathematical modeling as a way to help on finding the solution for timetabling. In this case, a timetable is a schedule or, more precisely, a list or table of events arranged according to the time when they take place. This text features new and useful software to optimize the use of human resources. The software is based on a mathematical model for determining the timetable while minimizing the number of students with conflicting schedules. © 2013 DIME UNIVERSITÀ DI GENOVA.
Keywords: Mathematical modeling; Optimization; Scheduling; Timetable